Does support from government help firms survive? Evidence on financial and political assistance in China, 1998–2007. Issue 5 (26th January 2019) - Qu, Tong; Harris, Richard
ABSTRACT: Using the National Bureau of Statistics data set over the period 1998–2007, this article examines the dual roles of financial assistance and strong political links on firm survival in China by applying a semi-parametric duration model. We find that generally either financial assistance or strong political links had a positive effect on the likelihood of firm survival. Furthermore, if firms received both types of support from government, their survival rate was around two times as high compared to only receiving a single support. The likelihood of survival depended on the amount of assistance a firm received. We also find firm ownership impacts on its survival pattern. Lastly, China joining the World Trade Organisation (WTO) coincided with (cet. par.) higher firm failure, especially with regard to state-owned firms; however, this period also saw the authorities targeting political and financial help on the 'better' firms (especially SOEs) with characteristics likely to increase their chance of survival.